Constructed heterostructured SnS@MoO3 hollow nanotubes and detected sensing properties towards TEA. (February 2021) - Ma, Y.T.; Ma, S.Y.; Tang, J.; Wu, Z.G.; Shi, J.; Zhao, Y.; Wang, Y.; Pei, S.T.
Abstract: To overcome the obstacle of triangular prism-like MoO3 nanorods (MoO3 ) gas sensor including low response, poor selectivity and a heavy influence of humidity to Triethylamine (TEA), heterostructured tin sulfide (SnS) composited with MoO3 hollow nanotubes (SnS@MoO3 ) were synthesised by a facilely hydrothermal method. Its morphology and structure were charactered through different technologies. The result indicated that the sensor based on SnS@MoO3 exhibited higher response (73.46%), shorter response/recovery time (8.1/4.5 s), excellently selectivity and anti-humidity properties than MoO3 to 50 ppm TEA at 250 °C. Thus, the SnS@MoO3 is a promising material for detecting TEA. Highlights: Heterostructured SnS@MoO3 hollow nanotubes were synthesised by hydrothermal method. The sensors of SnS@MoO3 has short response/recovery time (8.1/4.5 s) to TEA. The response of SnS@MoO3 sensor reaches 73.46% to 50 ppm TEA at 250 °C. The SnS@MoO3 sensor displays excellently selectivity and anti-humidity properties to TEA.